Efeito do tratamento do canal radicular com EDTA na retenção de pinos de fibra de vidro - Gordillo, Luis Alfonso Arana (2010)
The purpose of this study was to analyze the effect of the treatment of dentin with EDTA on the bond strength of a fiber post to dentin, using two different types of resin cements. A total of 40 single canal, sound extracted human bicuspids were selected. After extraction the teeth were stored in water until use. Post spaces were prepared in extracted premolars and then the root canals were subjected to one of the following four groups (n = 10): Group 1 - self-adhesive cement RelyXTM U100, Group 2 - etching with 24% EDTA for 60 s before applying the cement RelyXTM U100, Group 3 - cementation as recommended by the manufacturer with Para Post® Para CoreTM Automix and self-etching adhesive, Group 4 - etching with 24% EDTA for 60 s before application of Para Post® Para CoreTM Automix cement and self-etching adhesive. The 10 roots per group were cut perpendicular to the long axis of the tooth in 6 slides 1 mm for push-out test (two slides for root third). After cutting one slide for each third was subjected to thermal cycling test of 5000 cycles at 5 º C and 55 ° C the slides were randomly divided into two subgroups, depending on testing time (imMédiate vs. termocycling ), for push-out test. The push out test was performed at a speed of 0.5 mm / min. Data were analyzed with a one-way analysis of variance (ANOVA) and Tukey HSD test. ANOVA revealed that canal surface treatment with EDTA 24% affected the bond strength negatively at the cervical third of the two cements, but did not alter the bond strength of dentin cements tested in the middle and apical thirds in the imMédiate group, the group of thermocycling was no significant difference when compared with the group imMédiately with or without EDTA 24% for all groups tested Para Post® Para CoreTM Automix and self-etching adhesive showed higher bond strength values when compared with RelyXTM U100 resin cement. It was concluded that treatment with EDTA did not affect the bond strength except at the cervical third , EDTA 24% did not alter the of bond strength values in the groups of thermocycling test, the Para Post® Para CoreTM Automix and self-etching adhesive cement had better performance when compared with cement RelyXTM U100.